Higher Education's Panopticon? Learning Analytics, Ethics and Student Engagement. Issue 1 (March 2017) - Wintrup, Julie
Abstract Is learning analytics a movement that seeks to rebalance the effects of higher education's apparent blindness to privilege, its unequal access regimes and persistent retention and attainment gaps through a more skilful and strategic use of student data? Or is it part of a larger project to surveil students and staff in higher education, in pursuit of greater efficiency and control? Both perspectives are alive and well in debates surrounding higher education's changing relationship with its students. The systematic institutional use of student-generated data known as learning analytics is raising practical, methodological and ethical questions, which are yet to be answered. However, a proposed framework for assessing and comparing the quality of learning and teaching in the UK is poised to use such data as one of its metrics. Learning analytics and its relationship to student engagement is explored through the first known research to utilise an adaptation of Kuh's National Survey of Student Engagement with people studying Massive Open Online Courses. Contrasting perspectives are offered by Siemen's theory of connectivist learning and Foucault's notion of the panopticon. If the potential of analytics is to be realised in terms of meaningful quality improvement, questions remain concerning ethics, trust, its role in engagement in learning, and the ways in which policy might effectively safeguard the longer-term individual and collective interests of students.